One Year Overview and Follow-Up in a Post-COVID Consultation of Critically Ill Patients - González, Jessica; Zuil, María; Benítez, Iván D.; de Gonzalo-Calvo, David; Aguilar, María; Santisteve, Sally; Vaca, Rafaela; Minguez, Olga; Seck, Faty; Torres, Gerard; de Batlle, Jordi; Gómez, Silvia; et al. (Frontiers in Medicine, 2022)
The long-term clinical management and evolution of a cohort of critical COVID-19 survivors have not been described in detail. We report a prospective observational study of COVID-19 patients admitted to the ICU between March and August 2020. The follow-up in a post-COVID consultation comprised symptoms, pulmonary function tests, the 6-minute walking test (6MWT), and chest computed tomography (CT). Additionally, questionnaires to evaluate the prevalence of post-COVID-19 syndrome were administered at 1 year. A total of 181 patients were admitted to the ICU during the study period. They were middle-aged (median [IQR] of 61 [52;67]) and male (66.9%), with a median ICU stay of 9 (5-24.2) days. 20% died in the hospital, and 39 were not able to be included. A cohort of 105 patients initiated the follow-up. At one year, 32.2% persisted with respiratory alterations and needed to continue the follow-up. Ten percent still had moderate/severe lung diffusion (DLCO) involvement (<60%), and 53.7% had a fibrotic pattern on CT. Moreover, patients had a mean (SD) number of symptoms of 5.7±4.6, and 61.3% met the criteria for post-COVID syndrome at one year. During the follow-up, 46 patients were discharged, and 16 were transferred to other consultations. Other conditions, such as emphysema (21.6%), COPD (8.2%), severe neurocognitive disorders (4.1%) and lung cancer (1%), were identified. A high use of health care resources is observed in the first year. In conclusion, one-third of critically ill COVID-19 patients need to continue follow-up beyond one year, due to abnormalities on DLCO, chest CT or persistent symptoms.